(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Instilling a sense of patriotism and national identity in young students is a fundamental aspect of primary education in Uzbekistan. The 2nd grade textbook serves as a vital tool in introducing children to the concept of the Motherland through stories, poems, illustrations, and interactive methods. By integrating visual and experiential learning approaches such as field trips, discussions, and patriotic songs, educators nurture a deep connection between students and their homeland. This thesis explores how national identity is developed through these educational methods, fostering responsible citizenship.